(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Views on the etiology and pathogenesis of trigeminal neuralgia (TN) have changed as diagnostic and treatment methods have improved. The use of microvascular root decompression has shown high effectiveness, but relapses of the disease are observed